Pengaruh Terapi Relaksasi Otot Progressive Terhadap Kualitas Tidur Lansia di UPT Pelayanan Sosial Lanjut Usia Binjai tahun 2017 - Siregar, Rinco (Jurnal Ilmiah Keperawatan, 2018)
To determine the effect of progressive muscle relaxation therapy on quality of sleep in elderly  people at Binjai Senior Recident Social Service in 2017. One group pre-tes and post test, quasi-experimental design  was used in this study, 30 elderly people were selection with purposive sampling.  Quality of sleep in elderly peopole was measured by Pittsburgh Sleep Quality Index (PSQI. Comparative assessment on difference in quality of sleep of  elderly peopole before and after using Pair t- test. The result of this study found that  after receiving progressive muscle relaxation therapy for 4 weeks, every day, 15 minutes duration the quality of sleep in elderly  people at Binjai Senior Recident Social Service significantly  increased. (p  < .05). The progressive muscle relaxation therapy can use  as one of the intervention to improve the quality of sleep in elderly  people at Binjai Senior Recident Social Service  Indonesia.